2011
DOI: 10.1016/j.cell.2011.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Retrieval Strategies for Remote Memories

Abstract: Prevailing theory suggests that long-term memories are encoded via a two-phase process requiring early involvement of the hippocampus followed by the neocortex. Contextual fear memories in rodents rely on the hippocampus immediately following training but are unaffected by hippocampal lesions or pharmacological inhibition weeks later. With fast optogenetic methods, we examine the real-time contribution of hippocampal CA1 excitatory neurons to remote memory and find that contextual fear memory recall, even week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

48
443
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 495 publications
(492 citation statements)
references
References 48 publications
48
443
1
Order By: Relevance
“…Lesions or pharmacological inactivation of the hippocampus preferentially impact recently acquired contextual fear memory (Anagnostaras et al, 1999;de Oliveira Alvares et al, 2012;Goshen et al, 2011;Kitamura et al, 2009;Ward et al, 1999;Wiltgen et al, 2010;Winocur et al, 2009). Conversely, transient disruption of the anterior cingulate cortex (ACC) impairs the expression of remote, but not recent memory (Frankland et al, 2004;Goshen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lesions or pharmacological inactivation of the hippocampus preferentially impact recently acquired contextual fear memory (Anagnostaras et al, 1999;de Oliveira Alvares et al, 2012;Goshen et al, 2011;Kitamura et al, 2009;Ward et al, 1999;Wiltgen et al, 2010;Winocur et al, 2009). Conversely, transient disruption of the anterior cingulate cortex (ACC) impairs the expression of remote, but not recent memory (Frankland et al, 2004;Goshen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, transient disruption of the anterior cingulate cortex (ACC) impairs the expression of remote, but not recent memory (Frankland et al, 2004;Goshen et al, 2011). Such findings have led to the idea that the hippocampus serves a critical role in integrating information from a distributed cortical network representing various features of a memory, and that over time, the medial prefrontal cortex (including the ACC) gradually takes over this integrative role, allowing the memory to function independently of the hippocampus (Frankland and Bontempi, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…There are many cases of patients with memory loss after medial temporal amnesia with no temporal gradient, and it has been shown that the hippocampus may not only be involved in encoding, but may also contribute to storage and retrieval of memory [33,34]. Recent animal studies also showed that hippocampal memory was not merely replaced by the cortical one, but rather both memories are in continuous interplay and there may indeed be a default role for the hippocampus in remote memory recall [33,35,36,37,38]. Intriguing recent studies have shown a default role for the hippocampus in remote memory recall [37,39], including a study where optogenetic inhibition of the CA1 pyramidal neurons in the hippocampus was sufficient to impair remote recall of memories using the contextual fear conditioning learning paradigm [38].…”
Section: Discussionmentioning
confidence: 99%
“…Recent animal studies also showed that hippocampal memory was not merely replaced by the cortical one, but rather both memories are in continuous interplay and there may indeed be a default role for the hippocampus in remote memory recall [33,35,36,37,38]. Intriguing recent studies have shown a default role for the hippocampus in remote memory recall [37,39], including a study where optogenetic inhibition of the CA1 pyramidal neurons in the hippocampus was sufficient to impair remote recall of memories using the contextual fear conditioning learning paradigm [38]. In agreement with these recent developments in the understanding of the role of the hippocampus in long term memory, we observed that precise, real-time inhibition of GABAergic interneuron activity in the hilus of the hippocampus, using optogenetic techniques, impairs memory retrieval up to 2 weeks after the initial memory formation, highlighting the importance of the hilar inhibitory interneurons in long-term memory retrieval.…”
Section: Discussionmentioning
confidence: 99%
“…Goshen and colleagues demonstrated that photoinactivation of these neurons apparently inhibits both the acquisition and retrieval of remote fear memories while optogenetic reactivation of specific neuronal groups is sufficient to elicit a fear response [48] . On the other hand, optogenetics can be used to control epileptiform activity.…”
Section: Hippocampus Since Boyden Et Al (2005) Intro-mentioning
confidence: 99%